Calendars in the Dead Sea scrolls : measuring time - VanderKam, James C. (Literature of the Dead Sea scrolls., 1998)
Calendars in the Dead Sea Scrolls explores the evidence about calendars in the Dead Sea Scrolls, the Hebrew Bible and other ancient Jewish texts.